Multiple ossified spinal meningiomas in the thoracic spine: A case report and literature review - Dong, Chunke; Liu, Yi; Zhu, Yuting; Wei, Hongyu; Ma, Yuzhuo (Frontiers in Surgery, 2022)
Abstract Background: Ossified spinal meningioma (OSM) is a rare form of a spinal tumor. The surgical strategies and pathologic findings related to OSM have been investigated in recent years. However, multiple OSMs are rarely reported. Here we intend to present a rare case of multiple OSM and review the relevant published literature. Case Presentation: A 76-year-old woman experienced a progressive sensorimotor disturbance in her bilateral lower limbs for the past two years. She complained of inability to walk, urinary incontinence, and chronic constipation when referred to our hospital. Neurological examination revealed a diminished sensation below the bilateral T7, and neurological status was Nurick Grade 6. Magnetic resonance imaging (MRI) revealed multiple intradural-extramedullary neoplasms at the T7-T11 level. Computed tomography (CT) scans showed 5 high-density masses of varying sizes in the spinal canal at the T7-T12 level. The patient underwent tumor resection through T7-T11 laminectomy. Histopathological examination revealed multiple OSMs. Conclusion: We reported a rare case of multiple OSMs in an elderly patient. After one-stage complete resection, the patient recovered with satisfactory curative effect. Although elderly patients will face various postoperative complications due to poor physical condition, we still recommend one-stage complete resection of multiple OSMs to reduce recurrence.